Development and validation of the Pediatric Anesthesia Behavior score – an objective measure of behavior during induction of anesthesia. Issue 2 (19th September 2013) - Beringer, Richard M.; Greenwood, Rosemary; Kilpatrick, Nicky; Lerman, Jerrold
Summary Background Measuring perioperative behavior changes requires validated objective rating scales. We developed a simple score for children's behavior during induction of anesthesia (Pediatric Anesthesia Behavior score) and assessed its reliability, concurrent validity, and predictive validity. Methods Data were collected as part of a wider observational study of perioperative behavior changes in children undergoing general anesthesia for elective dental extractions. One‐hundred and two healthy children aged 2–12 were recruited. Previously validated behavioral scales were used as follows: the modified Yale Preoperative Anxiety Scale (m‐YPAS); the induction compliance checklist (ICC); the Pediatric Anesthesia Emergence Delirium scale (PAED); and the Post‐Hospitalization Behavior Questionnaire (PHBQ). Pediatric Anesthesia Behavior (PAB) score was independently measured by two investigators, to allow assessment of interobserver reliability. Concurrent validity was assessed by examining the correlation between the PAB score, the m‐YPAS, and the ICC. Predictive validity was assessed by examining the association between the PAB score, the PAED scale, and the PHBQ. Results The PAB score correlated strongly with both the m‐YPAS (P < 0.001) and the ICC (P < 0.001). PAB score was significantly associated with the PAED score (P = 0.031) and with the PHBQ (P = 0.034). Two independent investigators recorded identical PAB scores for 94% of children and overall, there was close agreement between scores (Kappa coefficient of 0.886 [P < 0.001]). Conclusion The PAB score is simple to use and may predict which children are at increased risk of developing postoperative behavioral disturbance. This study provides evidence for its reliability and validity.